Performance Evaluation of a Palm Oil Factory Using the Balanced Scorecard: A Case Study Approach - Nahulae, Leni Lastrian; Daulay, Aqwa Naser; Harahap, Isnaini (Pusat P2M Politeknik Negeri Batam, 2025)
The purpose of this study is to evaluate the performance of a palm oil mill using the Balanced Scorecard (BSC) model at PT. Perkebunan Nusantara IV Pasir Mandoge. This research employs a quantitative approach, utilizing numerical data and statistics to answer the research questions. The data consists of primary data collected through interviews and secondary data from financial reports at PTPN IV. The data were analyzed using the Balanced Scorecard concept, which divides performance measurements into financial and non-financial perspectives. The results of the study indicate that the financial perspective yields good performance results, which need to be maintained by increasing income through marketing efforts. This can be achieved by enhancing product innovation, improving efficiency on each production machine, and developing facilities and services to boost income, maximizing existing resources for optimal returns. From the customer's perspective, performance results are poor due to inadequate attention to customer complaints and feedback, as the company focuses more on growing its market share, rather than reducing complaints through customer retention and acquisition strategies. Recommendations for the customer perspective include minimizing defective products to ensure quality, maintaining strong customer relationships, and offering appealing incentives. From an internal business process perspective, improvements in company performance are evident, as demonstrated by faster processing times, which in turn lead to higher customer satisfaction. The operational perspective shows satisfactory results, as seen in monthly outputs compared to company averages. The learning and growth perspective indicates even better outcomes. An increase in the number of employees participating in training and development has a positive impact on employee performance, satisfaction, and productivity, ultimately benefiting the company in the long run.